ANTESEDEN INTENTION TO CONTINUOUS USE PENGGUNA E-WALLET DI JAKARTA: PERCEIVED USEFULNESS SEBAGAI VARIABEL MEDIASI - MELIZABETH; NUNO SUTRISNO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The purpose of this study was to determine and analyze the effect of perceived ease of use, perceived enjoyment, reward, and trust on intention to continuous use through perceived usefulness as a mediating variable among e-wallet users in Jakarta, with the goal of increasing e-wallet competitiveness in the fintech industry. This research design uses descriptive and causal research. The method of determining the sample using non-probability sampling with purposive sampling technique. The sample used as many as 273 respondents and data analysis using Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach using SmartPLS software. The results indicate that perceived ease of use, perceived enjoyment, reward, and trust have a positive effect on perceived usefulness. Furthermore, perceived ease of use, reward, trust, and perceived usefulness have a positive effect on intention to continuous use, whereas perceived enjoyment has no direct effect. The study also found that perceived usefulness successfully mediates the relationship between the independent variables and intention to continuous use.